Computational Estimates of Thermochemistry and pK(a) Values of Cyclopropenyl Imine Superbases - ÇİFTÇİOĞLU, GÖKÇEN ALEV (WILEY, 2014)
The thermochemical properties of superbase species derived from cyclopropeneimine are estimated by computations on systems of isodesmic reactions. Proton affinities, gas phase basicities, and pK(a) values are well represented by computations incorporating G4 and CBS-QB3 schemes augmented for large systems by DFT calculations with functionals M06-2X and B97DX in the cc-pVTZ Dunning basis. Our calculations show that relative base strengths in gas are enhanced by alkyl substitution, either by methyl groups or larger species. For acetonitrile solution, alkyl substitution seems to weaken the base. (c) 2013 Wiley Periodicals, Inc.
Keywords: superbases; proton affinities; basicity; density functional theory; DENSITY FUNCTIONALS; PROTON AFFINITIES; GAS-PHASE; HEAT